Cultural and Tourism Ambassador: Jaka Rara of Cirebon City in Building Personal Branding - Putri Amalia; Siti Khumayah; Aghnia Dian Lestari (Apollo: Journal of Tourism and Business, 2025)
Building a positive reputation in the community is an important part of personal branding, especially for those who serve as cultural representatives, such as Jaka Rara, the cultural and tourism ambassador of Cirebon City. In an effort to preserve the culture and local wisdom of Cirebon, social media serves as a strategic platform to introduce cultural values more widely to the community. This study aims to identify the strategies employed by Jaka Rara of Cirebon in building their personal brand as cultural and tourism ambassadors for the city of Cirebon. This qualitative research involves data collection through in-depth interviews, document analysis, and observation. The results of the research, using Peter Montoya's (2002) personal branding theory, show that Jaka Rara participants have successfully built specialization by strengthening their identity as a reflection of local culture, including the use of Cirebon's distinctive ornaments and mastery of cultural material. Additionally, the aspect of unity is evident in the consistency of cultural messages conveyed through various Instagram features, such as Q&A sessions, Instagram Live, responding to followers' comments, and creating contemporary content that reinforces the dissemination of tourism and cultural education about Cirebon City. This approach reflects the success of Jaka Rara Cirebon City in conveying cultural messages authentically and integrally.